Efficacy of cannabidiol in improving the quality of life with Parkinson’s Patient: integrative review (Research, Society and Development, 2021)
Objective: To investigate the applicability and benefits of cannabidiol therapy in improving the quality of life of patients with Parkinson's disease. Methodology: This is an integrative literature review where articles were selected using the platforms of BIREME, SCIENCE, EBSCO, PUBMED, LILACS and only complete articles in Portuguese, English and German and published among 1995 to 2020. Results: Given the facts, this article brought the effectiveness of cannabidiol for the treatment of first choice for Parkinson's disease, and to promote patients and their families a better coexistence with the disease, and positive effects in all areas for a better quality of life. Conclusion: Although cannabidiol has shown efficacy in the therapy of parkinsonian patients, the need for further studies and investigations regarding its therapeutic effects is still evident. Thus, cannabidiol could become the treatment of choice for PD, and promote better coexistence with the disease for patients and their families.